A method for preparing heat-resistant and impact-resistant polyamide plastic

By using homemade polyamide, elastomer microspheres, silane-modified glass fibers and lubricants, heat-resistant and impact-resistant polyamide plastics are prepared, which solves the degradation problem and impact-resistant properties of polyamide plastics under high temperature and ultraviolet rays. The poor problem achieves higher anti-aging and impact resistance.

CN118359918BActive Publication Date: 2025-02-18DONGGUAN YUANSHENG POLYMER MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410304139.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-03
Publication Date
2025-02-18
Estimated Expiration
2043-04-03

AI Technical Summary

Technical Problem

Existing polyamide plastics are prone to degradation under high temperature and ultraviolet rays, and have poor impact resistance, which affects their use.

Method used

The heat-resistant and impact-resistant polyamide plastic is prepared through specific process steps using raw materials such as homemade polyamide, elastomer microspheres, silane-modified glass fibers and lubricants.

Benefits of technology

It improves the anti-aging and impact resistance of polyamide plastics, and enhances its stability under high temperature and ultraviolet rays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a method for preparing heat-resistant and impact-resistant polyamide plastics, and relates to the field of plastic technology. The present invention first activates and swells the rubber, forms a multi-porous structure inside, then enriches iron ions in the pores, forms magnetic rubber by precipitation, and then polymerizes with N,N'-(1,2-dihydroxyethylene)bisacrylamide, ethylene, and diallyldiethoxysilane into magnetic elastomer microspheres, which play a toughening role in the plastic substrate and improve the impact resistance of the plastic; then 3-methoxy-1-bromobenzene, 3-amino-5-carboxyphenylboric acid, 4,4'-diamino-2,2'-bipyridine, copper ion solution, p-fluorobenzoyl chloride, hydroquinone, and trimethylchlorosilane are used to prepare homemade polyamide, which can inhibit photodegradation and thermal oxidation aging; then homemade polyamide, elastomer microspheres, silane-modified glass fibers, etc. are used as raw materials to prepare plastics. The polyamide plastic prepared by the present invention has the effects of impact resistance, anti-aging, and magnetic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastics, in particular to a method for preparing heat-resistant and impact-resistant polyamide plastics. Background Art

[0002] Polyamide plastic, also known as nylon plastic, is a widely used engineering plastic with good mechanical properties, heat resistance, wear resistance, chemical solvent resistance, self-lubrication and certain flame retardancy. It has excellent processing performance and can be integrated into complex structural parts. It is widely used in the fields of automobiles, electronic appliances, machinery, rail transportation, sports equipment, etc. The amide group in polyamide plastic has strong polarity and is easily affected by high temperature, ultraviolet rays and other environmental factors, causing cross-linking, chain breaking, isomerization and other reactions in the polymer chain, resulting in plastic degradation, discoloration, brittleness and performance degradation. In addition, the existing polyamide plastic has poor impact resistance. If a certain external force is applied, the plastic structure will be destroyed, affecting its use. Summary of the invention

[0003] The purpose of the present invention is to provide a heat-resistant and impact-resistant polyamide plastic and a preparation method thereof, so as to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a heat-resistant and impact-resistant polyamide plastic, wherein the heat-resistant and impact-resistant polyamide plastic comprises self-made polyamide, elastomeric microspheres, silane-modified glass fiber, and a lubricant.

[0005] Furthermore, the self-made polyamide is prepared from 3-methoxy-1-bromobenzene, 3-amino-5-carboxyphenylboric acid, 4,4'-diamino-2,2'-bipyridine, p-fluorobenzoyl chloride, hydroquinone, and trimethylsilyl chloride.

[0006] Furthermore, the elastomeric microspheres are prepared by the following method: after the waste rubber is activated and swollen with a porogen, it is mixed and soaked with deionized water, ferric chloride, and ferrous sulfate, and then a sodium hydroxide solution is added to co-precipitate the magnetic rubber; and then the elastomeric microspheres are prepared by polymerizing with N,N'-(1,2-dihydroxyethylene)bisacrylamide, n-hexane, diallyldiethoxysilane, and ethylene.

[0007] Furthermore, the lubricant is a mixture of one or more of stearic acid, stearate or polyethylene wax.

[0008] Furthermore, a method for preparing a heat-resistant and impact-resistant polyamide plastic comprises the following preparation steps:

[0009] (1) Mix a benzophenone compound, 4,4'-diamino-2,2'-bipyridine, triethylamine and tetrahydrofuran in a mass ratio of 1:0.3:1.4:50 to 1:0.5:1.4:55, stir at 60 rpm for 3 to 6 hours, and react at a vacuum degree of -0.09 MPa and 55°C for 4 to 5 hours to obtain intermediate B;

[0010] (2) Intermediate B and chloroform were mixed in a mass ratio of 1:97 to 1:103, nitrogen was introduced at 80 sccm for 30 min, and then a copper ion solution of 48 to 56 times the mass of intermediate B was added. After reacting at 50°C for 5 to 7 h, the precipitate was filtered and washed with double distilled water, acetone and anhydrous ether for 5 times, and dried at -0.07 MPa and 50°C for 8 h to obtain a copper complex;

[0011] (3) Deionized water, copper complex, sodium hydroxide and sodium dodecyl sulfate were mixed in a mass ratio of 7:1:0.5:0.01, stirred and dissolved, and then a 14-20 times mass of p-fluorobenzoyl chloride solution of the copper complex was added. After reacting at room temperature for 7-9 hours, the mixture was filtered, washed with deionized water for 3 times, and dried at 80°C for 4 hours to obtain intermediate C;

[0012] (4) Under nitrogen protection, the intermediate C, butyl ether and trimethylchlorosilane are mixed in a mass ratio of 1:4:1.4 to 1:5:3.0, the temperature is raised to 160°C, and the reaction is carried out for 14 to 16 hours to obtain a monomer compound; the monomer compound, hydroquinone, potassium carbonate, toluene and N-methylpyrrolidone are mixed in a mass ratio of 1:0.5:0.6:0.4:3 to 1:0.7:0.6:0.5:4, the temperature is raised to 160 to 180°C, the temperature is kept to react for 30 minutes, the temperature is raised to 195 to 202°C, the reaction is carried out for 5 to 6 hours, deionized water is poured into the mixture while hot, the mixture is filtered, and the mixture is washed with deionized water at 90°C for 5 times, the mixture is ground to pass through a 20 to 30 mesh sieve, the mixture is washed with deionized water at 90°C for 3 times, and the mixture is dried at 100°C for 6 hours to obtain a self-made polyamide;

[0013] (5) At 15°C, distilled water and 4.5% hydrochloric acid were mixed in a mass ratio of 170:1. After stirring evenly, homemade polyamide, elastomer microspheres, methyl dihydrogen disiloxane, anhydrous ethanol, 4.5% hydrochloric acid, and isohexadecane were added in a mass ratio of 1:0.2:0.5:0.4:0.05:1.4 to 1:0.3:0.6:0.4:0.05:1.4. The mass ratio of homemade polyamide to deionized water was 1:0.6. The temperature was raised to 90°C. After reacting for 2 to 4 hours, sodium bicarbonate was added to the reaction solution until the pH value was 7, and the mixture was washed with deionized water for 3 times. Diatomaceous earth (0.3 times the mass of the homemade polyamide) was added, and the mixture was allowed to stand for 30 minutes. The mixture was filtered and dried at 50°C and a vacuum degree of -0.07 MPa for 5 hours. Silane-modified glass fiber and lubricant were added at a mass ratio of 1:0.1. The mass ratio of silane-modified glass fiber to homemade polyamide was 0.1:1. After stirring and mixing, the mixture was extruded at 190 to 230°C and pelletized to obtain heat-resistant and impact-resistant polyamide plastic.

[0014] Furthermore, the preparation method of the benzophenone compound in step (1) is:

[0015] A. Mix 3-methoxy-1-bromobenzene, 1,2-dichloroethane and 3-amino-5-carboxyphenylboronic acid in a mass ratio of 1:16:0.7 to 1:16:1.0, place in an ice bath under argon protection, stir at 60 to 80 rpm for 10 min, add Eaton's reagent in an amount of 0.2 to 0.3 times the mass of 1,2-dichloroethane, continue stirring for 30 to 40 min, remove the ice bath, stir at room temperature for 30 min, heat to 30 to 40 ° C, react for 12 h, cool to room temperature, extract with water 3 times, take the organic layer, extract once with saturated brine, take the organic layer, dry at 90 ° C for 5 h to obtain intermediate A;

[0016] B. Mix the intermediate A and dichloromethane in a mass ratio of 1:130, place in an ice bath under nitrogen protection, stir at 60-80 rpm for 10 min, add a boron tribromide solution 14-18 times the mass of the intermediate A, the mass ratio of boron tribromide to dichloromethane in the boron tribromide solution is 1:4.88, react for 25-35 min, move to room temperature to react for 3-4 h, add methanol until no smoke evaporates, then add sodium hydroxide solution until the solution pH is 8-9, separate the liquids, add hydrochloric acid until the solution pH is 4-5, extract with ethyl acetate 3 times, take the organic layer, vacuum degree -0.07 MPa, 55 ° C dry for 6 h to obtain benzophenone compound.

[0017] Furthermore, the copper ion solution in step (2) is a mixture of copper tetraethyl cyanide hexafluorophosphate and methanol in a mass ratio of 1:79.1.

[0018] Furthermore, the p-fluorobenzoyl chloride solution in step (3) is p-fluorobenzoyl chloride and dichloromethane in a mass ratio of 1:8.3.

[0019] Furthermore, the preparation method of the elastomeric microspheres in step (5) is:

[0020] a. Mix waste rubber, sodium dodecylbenzene sulfonate and deionized water in a mass ratio of 1:0.6:80 to 1:2.6:100, and ultrasonicate at 30 to 40°C and 600W for 12 to 20 minutes, then add dibutyl phthalate in an amount of 1 to 5 times the mass of the waste rubber, activate at 40 to 60°C for 48 to 60 hours, and then add n-heptane in an amount of 15 to 20 times the mass of the waste rubber, and react at 40 to 60°C for 24 to 30 hours to obtain swollen rubber;

[0021] b. Mix deionized water, ferric chloride, ferrous sulfate and swollen rubber in a mass ratio of 4:1.4:1.0:1 to 4:2.0:1.2:1, soak at 40°C for 4 to 5 hours, filter, add 4% sodium hydroxide solution with a mass fraction of 10 to 12 times the mass of the swollen rubber, react at 70 to 80°C for 1 hour, add hydrazine hydrate with a mass fraction of 0.1 times the mass of the swollen rubber, cool to 50°C, react for 30 minutes, separate magnetically, wash with deionized water until the pH of the washing solution is 7, and obtain magnetic rubber;

[0022] c. At 120°C, evacuate to 1-5Pa, replace with nitrogen 3 times, introduce ethylene to a pressure of 2MPa, add magnetic rubber, N,N'-(1,2-dihydroxyethylene)bisacrylamide, n-hexane, and diallyldiethoxysilane in a mass ratio of 1:0.3:0.9:0.2-1:0.4:1.2:0.3, mix, cool to 60°C, add triisobutylaluminum (0.005 times the mass of magnetic rubber) and initiator VOCl3-Al(C2H5)2Cl (0.01 times the mass of magnetic rubber), heat to 150°C, react for 10-30min, filter, wash with anhydrous ether 5 times, vacuum -0.07MPa, and dry at 50°C for 6h to obtain elastomeric microspheres.

[0023] Furthermore, the preparation method of the silane-modified glass fiber in step (5) is as follows: placing the glass fiber in a coupling agent solution at a material-liquid ratio of 1:20, wherein the mass ratio of the coupling agent KH-550 to anhydrous ethanol in the coupling agent solution is 1:24 to 1:49, soaking for 15 minutes, taking it out, leaving it at room temperature for 1 hour, extracting it with xylene for 3 hours, washing it with anhydrous ethanol for 3 times, and drying it at 120° C. for 10 minutes to obtain the silane-modified glass fiber.

[0024] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0025] The invention uses self-made polyamide, elastomer microspheres and the like as raw materials to prepare polyamide plastics to achieve the effects of impact resistance, magnetic conductivity and anti-aging.

[0026] Firstly, the present invention utilizes the reaction of the aromatic group of 3-methoxy-1-bromobenzene with the carboxyl group of 3-amino-5-carboxylphenylboronic acid, and then demethylates the methoxyl group to form a hydroxyl group, thereby obtaining a benzophenone compound, which effectively absorbs ultraviolet light, prevents plastic from photodegradation, and improves the anti-aging performance of the plastic; the bromide ion reacts with part of the amino groups of 4,4'-diamino-2,2'-bipyridine, and the bipyridine cooperates with the cuprous ion, and the presence of the cuprous ion can generate negative ions with peroxyl radicals to inhibit oxidation, and the cuprous ion can be continuously regenerated through oxidation, reduction reaction and free radical capture, thereby delaying thermal oxidation aging. Then, under the bridging effect of p-fluorobenzoyl chloride, the amino group polymerizes with the hydroxyl group of hydroquinone to form polyamide, and at the same time, the boric acid structure reacts with the chloride ions of trimethylchlorosilane to introduce silicon and boron elements. During the heating process, they combine with the oxygen element in the air to form inorganic substances such as silicon oxide and boron oxide, thereby forming an isolation layer at the gas-solid interface to prevent the air from corroding the inner structure. When the temperature rises to a high temperature, the silicon and boron elements will be further converted into ceramic structures such as silicon carbide and boron carbide to prevent the plastic from continuing to thermally decompose and enhance the anti-aging performance of the plastic.

[0027] Secondly, after the rubber is activated and swollen, the porogen forms channels inside the rubber, and then it is immersed in an iron ion solution, so that ferrous ions and ferric ions are enriched in the pores. Under the action of sodium hydroxide, the iron ions in the pores are precipitated to form magnetic particles. Then the rubber is polymerized with N,N'-(1,2-dihydroxyethylene)bisacrylamide, ethylene, and diallyldiethoxysilane to form magnetic elastomer microspheres, which play a toughening phase role in the plastic substrate and improve the impact resistance of the plastic. Then, under the bridging effect of methyldihydrodisiloxane, the elastomer microspheres The siloxane on the surface polymerizes with the siloxane in the side chain of the polyamide molecule to form polysiloxane, which not only improves resistance to UV aging, but also facilitates the dispersion of the elastomer in the polyamide, and can induce and terminate silver streaks in large quantities during the impact process, thereby absorbing a large amount of impact energy to achieve an impact-resistant effect; in addition, the polar groups of the magnetic elastomer microspheres and the long-chain ends of the silane coupling agent in the glass fiber generate a strong attraction through the van der Waals force, overlapping each other to build a magnetic conductive network, and also promoting the strengthening and toughening effect of the glass fiber on the matrix polyamide. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the heat-resistant and impact-resistant polyamide plastics prepared in the following examples are as follows:

[0030] Impact resistance: The same mass of the embodiment and the comparative example was injected into standard test strips by a plastic injection molding machine, and the notched impact strength was tested according to GB / T1043.

[0031] Magnetic conductivity: The same mass of the embodiment and the comparative example was injection molded into standard test strips by a plastic injection molding machine, and the coercive force, maximum magnetic energy area and magnetic energy density were tested by a DMT-1 permanent magnetic material tester.

[0032] Anti-aging: The same mass of the embodiment and the comparative example was injected into standard test strips by a plastic injection molding machine, and the light-heat aging test was carried out according to ASTM G154 Cycle 1. The conditions were: the ultraviolet wavelength was 340nm, the irradiation intensity was 0.89W / (m 2 ·nm), the irradiation cycle is 8 hours of ultraviolet irradiation / blackboard temperature is 60℃, 4 hours of condensation / blackboard temperature is 50℃, the total test time is 1000 hours, and then refer to GB / T1043 to test the notched impact strength after aging.

[0033] Example 1

[0034] (1) 3-methoxy-1-bromobenzene, 1,2-dichloroethane and 3-amino-5-carboxyphenylboronic acid were mixed in a mass ratio of 1:16:0.7, placed in an ice bath under argon protection, stirred at 60 rpm for 10 min, and then 0.2 times the mass of Eaton's reagent of 1,2-dichloroethane was added. After stirring for 30 min, the ice bath was removed, and the mixture was stirred at room temperature for 30 min. The mixture was heated to 30°C and reacted for 12 h. The mixture was cooled to room temperature and extracted with water for 3 times. The organic layer was taken and extracted once with saturated brine. The organic layer was taken and dried at 90°C for 5 h to obtain intermediate A.

[0035] (2) Intermediate A and dichloromethane were mixed in a mass ratio of 1:130, placed in an ice bath under nitrogen protection, stirred at 60 rpm for 10 min, and a boron tribromide solution 14 times the mass of intermediate A was added. The mass ratio of boron tribromide to dichloromethane in the boron tribromide solution was 1:4.88. The mixture was reacted for 25 min, and then moved to room temperature for 3 h. Methanol was added until no smoke was generated, and then sodium hydroxide solution was added until the pH of the solution was 8. The mixture was separated, and hydrochloric acid was added until the pH of the solution was 4. The mixture was extracted with ethyl acetate 3 times. The organic layer was taken and dried at 55°C for 6 h under a vacuum degree of -0.07 MPa to obtain a benzophenone compound.

[0036] (3) Mix benzophenone compound, 4,4'-diamino-2,2'-bipyridine, triethylamine and tetrahydrofuran in a mass ratio of 1:0.3:1.4:50, stir at 60 rpm for 3 h, and react at a vacuum degree of -0.09 MPa and 55°C for 4 h to obtain intermediate B;

[0037] (4) Intermediate B and chloroform were mixed in a mass ratio of 1:97, nitrogen was introduced at 80 sccm for 30 min, and then a copper ion solution 48 times the mass of intermediate B was added. The mass ratio of copper tetraethyl cyanide hexafluorophosphate to methanol in the copper ion solution was 1:79.1. After reacting at 50°C for 5 h, the precipitate was filtered and washed with double distilled water, acetone and anhydrous ether for 5 times, and dried at -0.07 MPa and 50°C for 8 h to obtain a copper complex;

[0038] (5) Deionized water, copper complex, sodium hydroxide and sodium dodecyl sulfate were mixed in a mass ratio of 7:1:0.5:0.01, stirred and dissolved, and then a p-fluorobenzoyl chloride solution with a mass ratio of 14 times that of the copper complex was added, wherein the mass ratio of p-fluorobenzoyl chloride to dichloromethane in the p-fluorobenzoyl chloride solution was 1:8.3. After reacting at room temperature for 7 hours, the mixture was filtered, washed with deionized water for 3 times, and dried at 80°C for 4 hours to obtain intermediate C;

[0039] (6) Under nitrogen protection, the intermediate C, butyl ether, and trimethylchlorosilane were mixed in a mass ratio of 1:4:1.4, heated to 160°C, and reacted for 14 hours to obtain a monomer compound; the monomer compound, hydroquinone, potassium carbonate, toluene, and N-methylpyrrolidone were mixed in a mass ratio of 1:0.5:0.6:0.4:3, heated to 160°C, kept warm for 30 minutes, heated to 195°C, reacted for 5 hours, poured into deionized water while hot, filtered, washed with 90°C deionized water for 5 times, ground to pass through a 20-mesh sieve, washed with 90°C deionized water for 3 times, and dried at 100°C for 6 hours to obtain a homemade polyamide;

[0040] (7) Waste rubber, sodium dodecylbenzene sulfonate and deionized water were mixed in a mass ratio of 1:0.6:80, and ultrasonicated at 30°C and 600W for 12 minutes. Then, dibutyl phthalate (1 times the mass of the waste rubber) was added. After activation at 40°C for 48 hours, n-heptane (15 times the mass of the waste rubber) was added, and the mixture was reacted at 40°C for 24 hours to obtain swollen rubber.

[0041] (8) Deionized water, ferric chloride, ferrous sulfate, and swollen rubber were mixed in a mass ratio of 4:1.4:1:1, soaked at 40°C for 4 hours, filtered, 10 times the mass of the swollen rubber was added with a 4% sodium hydroxide solution, reacted at 70°C for 1 hour, and 0.1 times the mass of the swollen rubber was added with hydrazine hydrate. The temperature was lowered to 50°C, reacted for 30 minutes, magnetically separated, and washed with deionized water until the pH of the washing solution was 7 to obtain magnetic rubber;

[0042] (9) At 120°C, evacuate to 1Pa, replace with nitrogen three times, introduce ethylene to a pressure of 2MPa, add magnetic rubber, N,N'-(1,2-dihydroxyethylene)bisacrylamide, n-hexane, and diallyldiethoxysilane in a mass ratio of 1:0.3:0.9:0.2, cool to 60°C, add triisobutylaluminum (0.005 times the mass of magnetic rubber) and initiator VOCl3-Al(C2H5)2Cl (0.01 times the mass of magnetic rubber), heat to 150°C, react for 10 minutes, filter, wash with anhydrous ether five times, vacuum -0.07MPa, and dry at 50°C for 6 hours to obtain elastomeric microspheres;

[0043] (10) The glass fiber was placed in a coupling agent solution at a material-liquid ratio of 1:20, wherein the mass ratio of coupling agent KH-550 to anhydrous ethanol in the coupling agent solution was 1:24, and after soaking for 15 minutes, it was taken out, left at room temperature for 1 hour, extracted with xylene for 3 hours, and then washed with anhydrous ethanol for 3 times, and then dried at 120°C for 10 minutes to obtain silane-modified glass fiber;

[0044] (11) At 15°C, distilled water and 4.5% hydrochloric acid were mixed in a mass ratio of 170:1. After stirring evenly, homemade polyamide, elastomer microspheres, methyl dihydrogen disiloxane, anhydrous ethanol, 4.5% hydrochloric acid, and isohexadecane were added in a mass ratio of 1:0.2:0.5:0.4:0.05:1.4. The mass ratio of homemade polyamide to deionized water was 1:0.6. The temperature was raised to 90°C. After reacting for 2 h, carbon was added. Sodium bicarbonate is added until the pH value of the reaction liquid is 7, washed with deionized water for 3 times, diatomaceous earth (0.3 times the mass of the homemade polyamide) is added, allowed to stand for 30 minutes, filtered, dried at 50°C and vacuum degree of -0.07MPa for 5 hours, silane-modified glass fiber and stearic acid are added in a mass ratio of 1:0.1, and the mass ratio of silane-modified glass fiber to homemade polyamide is 0.1:1. After stirring and mixing, extrude at 190-230°C, and pelletize to obtain heat-resistant and impact-resistant polyamide plastic.

[0045] Example 2

[0046] (1) 3-methoxy-1-bromobenzene, 1,2-dichloroethane and 3-amino-5-carboxyphenylboronic acid were mixed in a mass ratio of 1:16:0.85, placed in an ice bath under argon protection, stirred at 70 rpm for 10 min, and then 0.25 times the mass of Eaton's reagent of 1,2-dichloroethane was added. After stirring for 35 min, the ice bath was removed, and the mixture was stirred at room temperature for 30 min. The mixture was heated to 35°C and reacted for 12 h. The mixture was cooled to room temperature and extracted with water for 3 times. The organic layer was taken and extracted once with saturated brine. The organic layer was taken and dried at 90°C for 5 h to obtain intermediate A.

[0047] (2) Mix intermediate A and dichloromethane in a mass ratio of 1:130, place in an ice bath under nitrogen protection, stir at 70 rpm for 10 min, add boron tribromide solution 16 times the mass of intermediate A, the mass ratio of boron tribromide to dichloromethane in the boron tribromide solution is 1:4.88, react for 30 min, move to room temperature for 3.5 h, add methanol until no smoke evaporates, then add sodium hydroxide solution until the solution pH is 8.5, separate the liquids, add hydrochloric acid until the solution pH is 4.5, extract with ethyl acetate 3 times, take the organic layer, vacuum degree -0.07 MPa, dry at 55 ° C for 6 h to obtain benzophenone compound;

[0048] (3) Mix benzophenone compound, 4,4'-diamino-2,2'-bipyridine, triethylamine and tetrahydrofuran in a mass ratio of 1:0.4:1.4:52.5, stir at 60 rpm for 4.5 h, and react at a vacuum degree of -0.09 MPa and 55°C for 4.5 h to obtain intermediate B;

[0049] (4) Intermediate B and chloroform were mixed in a mass ratio of 1:100, nitrogen was introduced at 80 sccm for 30 min, and then a copper ion solution with a mass ratio of 52 times that of intermediate B was added. The mass ratio of copper tetraethyl cyanide hexafluorophosphate to methanol in the copper ion solution was 1:79.1. After reacting at 50°C for 6 h, the precipitate was filtered and washed with double distilled water, acetone and anhydrous ether for 5 times, and dried at -0.07 MPa and 50°C for 8 h to obtain a copper complex;

[0050] (5) Deionized water, copper complex, sodium hydroxide and sodium dodecyl sulfate were mixed in a mass ratio of 7:1:0.5:0.01, stirred and dissolved, and then a p-fluorobenzoyl chloride solution with a mass ratio of 17 times that of the copper complex was added, wherein the mass ratio of p-fluorobenzoyl chloride to dichloromethane in the p-fluorobenzoyl chloride solution was 1:8.3. After reacting at room temperature for 8 hours, the mixture was filtered, washed with deionized water for 3 times, and dried at 80°C for 4 hours to obtain intermediate C;

[0051] (6) Under nitrogen protection, the intermediate C, butyl ether, and trimethylchlorosilane were mixed in a mass ratio of 1:4.5:2.2, heated to 160°C, and reacted for 15 hours to obtain a monomer compound. The monomer compound, hydroquinone, potassium carbonate, toluene, and N-methylpyrrolidone were mixed in a mass ratio of 1:0.6:0.6:0.45:3.5, heated to 170°C, kept warm for 30 minutes, heated to 198°C, reacted for 5.5 hours, poured into deionized water while hot, filtered, washed with 90°C deionized water for 5 times, ground to pass through a 25-mesh sieve, washed with 90°C deionized water for 3 times, and dried at 100°C for 6 hours to obtain a homemade polyamide;

[0052] (7) Waste rubber, sodium dodecylbenzene sulfonate and deionized water were mixed in a mass ratio of 1:1.6:90, and ultrasonicated at 35°C and 600W for 16 min. Then, dibutyl phthalate (3 times the mass of the waste rubber) was added. After activation at 50°C for 54 h, n-heptane (17.5 times the mass of the waste rubber) was added, and the mixture was reacted at 50°C for 27 h to obtain swollen rubber.

[0053] (8) Deionized water, ferric chloride, ferrous sulfate, and swollen rubber were mixed in a mass ratio of 4:1.7:1.5:1, soaked at 40°C for 4.5 hours, filtered, 11 times the mass of the swollen rubber in a 4% sodium hydroxide solution, reacted at 75°C for 1 hour, and 0.1 times the mass of the swollen rubber in hydrazine hydrate. The mixture was cooled to 50°C, reacted for 30 minutes, magnetically separated, and washed with deionized water until the pH of the washing solution was 7 to obtain magnetic rubber;

[0054] (9) At 120°C, evacuate to 3Pa, replace with nitrogen three times, introduce ethylene to a pressure of 2MPa, add magnetic rubber, N,N'-(1,2-dihydroxyethylene)bisacrylamide, n-hexane, and diallyldiethoxysilane in a mass ratio of 1:0.35:1.05:0.25, cool to 60°C, add triisobutylaluminum (0.005 times the mass of magnetic rubber) and initiator VOCl3-Al(C2H5)2Cl (0.01 times the mass of magnetic rubber), heat to 150°C, react for 20 minutes, filter, wash with anhydrous ether five times, vacuum -0.07MPa, and dry at 50°C for 6 hours to obtain elastomeric microspheres;

[0055] (10) The glass fiber was placed in a coupling agent solution at a material-liquid ratio of 1:20, wherein the mass ratio of coupling agent KH-550 to anhydrous ethanol in the coupling agent solution was 1:36.5, and after soaking for 15 minutes, it was taken out, left at room temperature for 1 hour, extracted with xylene for 3 hours, washed with anhydrous ethanol for 3 times, and dried at 120°C for 10 minutes to obtain silane-modified glass fiber;

[0056] (11) At 15°C, distilled water and 4.5% hydrochloric acid were mixed in a mass ratio of 170:1. After stirring evenly, homemade polyamide, elastomer microspheres, methyl dihydrogen disiloxane, anhydrous ethanol, 4.5% hydrochloric acid, and isohexadecane were added in a mass ratio of 1:0.25:0.55:0.4:0.05:1.4. The mass ratio of homemade polyamide to deionized water was 1:0.6. The temperature was raised to 90°C. After reacting for 3 hours, the mixture was added. Sodium bicarbonate was added until the pH value of the reaction liquid was 7, washed with deionized water for 3 times, diatomaceous earth (0.3 times the mass of the homemade polyamide) was added, allowed to stand for 30 minutes, filtered, dried at 50°C and vacuum degree of -0.07MPa for 5 hours, silane-modified glass fiber and stearate were added in a mass ratio of 1:0.1, and the mass ratio of silane-modified glass fiber to homemade polyamide was 0.1:1. After stirring and mixing, extruded at 190-230°C, and pelletized to obtain heat-resistant and impact-resistant polyamide plastic.

[0057] Example 3

[0058] (1) 3-methoxy-1-bromobenzene, 1,2-dichloroethane and 3-amino-5-carboxyphenylboronic acid were mixed in a mass ratio of 1:16:1, placed in an ice bath under argon protection, stirred at 80 rpm for 10 min, and then 0.3 times the mass of Eaton's reagent of 1,2-dichloroethane was added. After stirring for 40 min, the ice bath was removed, and the mixture was stirred at room temperature for 30 min. The mixture was heated to 40°C and reacted for 12 h. The mixture was cooled to room temperature and extracted with water for 3 times. The organic layer was taken and extracted once with saturated brine. The organic layer was taken and dried at 90°C for 5 h to obtain intermediate A.

[0059] (2) Intermediate A and dichloromethane were mixed in a mass ratio of 1:130, placed in an ice bath under nitrogen protection, stirred at 80 rpm for 10 min, and a boron tribromide solution 18 times the mass of intermediate A was added. The mass ratio of boron tribromide to dichloromethane in the boron tribromide solution was 1:4.88. The mixture was reacted for 35 min, moved to room temperature for 4 h, and methanol was added until no smoke was generated. Then, sodium hydroxide solution was added until the pH of the solution was 9. The mixture was separated, and hydrochloric acid was added until the pH of the solution was 5. The mixture was extracted with ethyl acetate for 3 times. The organic layer was taken and dried at 55°C for 6 h under a vacuum degree of -0.07 MPa to obtain a benzophenone compound.

[0060] (3) Mix benzophenone compound, 4,4'-diamino-2,2'-bipyridine, triethylamine and tetrahydrofuran in a mass ratio of 1:0.5:1.4:55, stir at 60 rpm for 6 h, and react at a vacuum degree of -0.09 MPa and 55°C for 5 h to obtain intermediate B;

[0061] (4) Intermediate B and chloroform were mixed in a mass ratio of 1:103, nitrogen was introduced at 80 sccm for 30 min, and then a copper ion solution with a mass ratio of 56 times that of intermediate B was added. The mass ratio of copper tetraethyl cyanide hexafluorophosphate to methanol in the copper ion solution was 1:79.1. After reacting at 50°C for 7 h, the precipitate was filtered and washed with double distilled water, acetone and anhydrous ether for 5 times, and dried at -0.07 MPa at 50°C for 8 h to obtain a copper complex;

[0062] (5) Deionized water, copper complex, sodium hydroxide and sodium dodecyl sulfate were mixed in a mass ratio of 7:1:0.5:0.01, stirred and dissolved, and then a p-fluorobenzoyl chloride solution with a mass ratio of 20 times that of the copper complex was added, wherein the mass ratio of p-fluorobenzoyl chloride to dichloromethane in the p-fluorobenzoyl chloride solution was 1:8.3. After reacting at room temperature for 9 hours, the mixture was filtered, washed with deionized water for 3 times, and dried at 80°C for 4 hours to obtain intermediate C;

[0063] (6) Under nitrogen protection, the intermediate C, butyl ether, and trimethylchlorosilane were mixed in a mass ratio of 1:5:3, heated to 160°C, and reacted for 16 hours to obtain a monomer compound. The monomer compound, hydroquinone, potassium carbonate, toluene, and N-methylpyrrolidone were mixed in a mass ratio of 1:0.7:0.6:0.5:4, heated to 180°C, kept warm for 30 minutes, heated to 202°C, reacted for 6 hours, poured into deionized water while hot, filtered, washed with 90°C deionized water for 5 times, ground to pass through a 30-mesh sieve, washed with 90°C deionized water for 3 times, and dried at 100°C for 6 hours to obtain a homemade polyamide;

[0064] (7) Mix waste rubber, sodium dodecylbenzene sulfonate and deionized water in a mass ratio of 1:2.6:100, and ultrasonicate at 40°C and 600W for 20 minutes. Then, add dibutyl phthalate (5 times the mass of the waste rubber), activate at 60°C for 60 hours, and then add n-heptane (20 times the mass of the waste rubber). React at 60°C for 30 hours to obtain swollen rubber.

[0065] (8) Deionized water, ferric chloride, ferrous sulfate, and swollen rubber were mixed in a mass ratio of 4:2:1.2:1, soaked at 40°C for 5 hours, filtered, 12 times the mass of the swollen rubber in a 4% sodium hydroxide solution, reacted at 80°C for 1 hour, and 0.1 times the mass of the swollen rubber in hydrazine hydrate. The mixture was cooled to 50°C, reacted for 30 minutes, magnetically separated, and washed with deionized water until the pH of the washing solution was 7 to obtain magnetic rubber.

[0066] (9) At 120°C, evacuate to 5 Pa, replace with nitrogen three times, introduce ethylene to a pressure of 2 MPa, add magnetic rubber, N,N'-(1,2-dihydroxyethylene)bisacrylamide, n-hexane, and diallyldiethoxysilane in a mass ratio of 1:0.4:1.2:0.3, mix, cool to 60°C, add triisobutylaluminum (0.005 times the mass of magnetic rubber) and initiator VOCl3-Al(C2H5)2Cl (0.01 times the mass of magnetic rubber), heat to 150°C, react for 30 min, filter, wash with anhydrous ether five times, vacuum -0.07 MPa, and dry at 50°C for 6 h to obtain elastomeric microspheres;

[0067] (10) The glass fiber was placed in a coupling agent solution at a material-liquid ratio of 1:20, wherein the mass ratio of coupling agent KH-550 to anhydrous ethanol in the coupling agent solution was 1:49, and after soaking for 15 minutes, it was taken out, placed at room temperature for 1 hour, extracted with xylene for 3 hours, and then washed with anhydrous ethanol for 3 times, and then dried at 120°C for 10 minutes to obtain silane-modified glass fiber;

[0068] (11) At 15°C, distilled water and 4.5% hydrochloric acid were mixed in a mass ratio of 170:1. After stirring evenly, homemade polyamide, elastomer microspheres, methyl dihydrogen disiloxane, anhydrous ethanol, 4.5% hydrochloric acid, and isohexadecane were added in a mass ratio of 1:0.3:0.6:0.4:0.05:1.4. The mass ratio of homemade polyamide to deionized water was 1:0.6. The temperature was raised to 90°C. After reacting for 4 hours, carbon was added. Sodium bicarbonate is added until the pH value of the reaction liquid is 7, washed with deionized water for 3 times, diatomaceous earth (0.3 times the mass of the homemade polyamide) is added, allowed to stand for 30 minutes, filtered, dried at 50°C and vacuum degree of -0.07MPa for 5 hours, silane-modified glass fiber and polyethylene wax are added in a mass ratio of 1:0.1, and the mass ratio of silane-modified glass fiber to homemade polyamide is 0.1:1. After stirring and mixing, extrude at 190-230°C, and pelletize to obtain heat-resistant and impact-resistant polyamide plastic.

[0069] Comparative Example 1

[0070] The difference between Comparative Example 1 and Example 2 is that there are no steps (1) and (2), and step (3) is changed to: 3-methoxy-1-bromobenzene, 4,4'-diamino-2,2'-bipyridine, triethylamine and tetrahydrofuran are mixed in a mass ratio of 1:0.4:1.4:52.5, stirred at 60 rpm for 4.5 hours, and then reacted at a vacuum degree of -0.09 MPa and 55° C. for 4.5 hours to obtain intermediate B. The remaining steps are the same as those in Example 2.

[0071] Comparative Example 2

[0072] The difference between Comparative Example 2 and Example 2 is that there are no steps (3) and (4), and step (5) is changed to: deionized water, benzophenone compound, sodium hydroxide, and sodium dodecyl sulfate are mixed in a mass ratio of 7:1:0.5:0.01, stirred and dissolved, and then a p-fluorobenzoyl chloride solution with a mass ratio of 17 times that of the benzophenone compound is added, and the mass ratio of p-fluorobenzoyl chloride to dichloromethane in the p-fluorobenzoyl chloride solution is 1:8.3. After reacting at room temperature for 8 hours, the mixture is filtered, washed with deionized water 3 times, and dried at 80° C. for 4 hours to obtain intermediate C. The remaining steps are the same as those in Example 2.

[0073] Comparative Example 3

[0074] The difference between Comparative Example 3 and Example 2 is that step (6) is changed to: Under nitrogen protection, intermediate C, hydroquinone, potassium carbonate, toluene, and N-methylpyrrolidone are mixed in a mass ratio of 1:0.6:0.6:0.45:3.5, heated to 170°C, kept warm for reaction for 30 minutes, then heated to 198°C, reacted for 5.5 hours, poured into deionized water while hot, filtered, washed with 90°C deionized water 5 times, ground to pass through a 25-mesh sieve, washed with 90°C deionized water 3 times, and dried at 100°C for 6 hours to obtain the self-made polyamide. The remaining steps are the same as those of Example 2.

[0075] Comparative Example 4

[0076] The difference between Comparative Example 4 and Example 2 is that there is no step (8), and step (9) is changed to: at 120° C., evacuate to 3 Pa, replace with nitrogen 3 times, introduce ethylene to a pressure of 2 MPa, add swollen rubber, N,N'-(1,2-dihydroxyethylene)bisacrylamide, n-hexane, and diallyldiethoxysilane in a mass ratio of 1:0.35:1.05:0.25, mix, cool to 60° C., add triisobutylaluminum in an amount of 0.005 times the mass of the swollen rubber and initiator VOCl3-Al(C2H5)2Cl in an amount of 0.01 times the mass of the swollen rubber, raise the temperature to 150° C., react for 20 min, filter, wash with anhydrous ether 5 times, vacuum degree -0.07 MPa, and dry at 50° C. for 6 h to obtain elastomeric microspheres. The remaining steps are the same as those of Example 2.

[0077] Comparative Example 5

[0078] The difference between Comparative Example 5 and Example 2 is that there are no steps (7) to (9), and step (11) is changed to: at 15°C, distilled water and hydrochloric acid with a mass fraction of 4.5% are mixed in a mass ratio of 170:1, stirred evenly, and then homemade polyamide, methyl dihydrogen disiloxane, anhydrous ethanol, hydrochloric acid with a mass fraction of 4.5%, and isohexadecane are added in a mass ratio of 1:0.55:0.4:0.05:1.4, and the mass ratio of homemade polyamide to deionized water is 1:0.6, and the temperature is raised to 90°C. After reacting for 3 hours, sodium bicarbonate was added until the pH of the reaction solution was 7, washed with deionized water for 3 times, diatomaceous earth 0.3 times the mass of the homemade polyamide was added, allowed to stand for 30 minutes, filtered, dried for 5 hours at 50°C and vacuum degree -0.07MPa, silane-modified glass fiber and stearate were added at a mass ratio of 1:0.1, and the mass ratio of silane-modified glass fiber to homemade polyamide was 0.1:1. After stirring and mixing, extruded at 190-230°C, pelletized, and heat-resistant and impact-resistant polyamide plastic was obtained. The remaining steps are the same as in Example 2.

[0079] Effect example

[0080] Table 1 below shows the performance analysis results of the heat-resistant and impact-resistant polyamide plastics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.

[0081] Table 1

[0082]

[0083] From the comparison of the impact strength and magnetic data experimental data of the embodiment and the comparative example, it can be found that the present invention first activates the rubber and swells the porogen to form a multi-porous structure inside, so that ferrous ions and ferric ions are enriched in the pores, and under the action of sodium hydroxide, the ferric ions in the pores are precipitated to form magnetic rubber, and then the rubber is polymerized with N,N'-(1,2-dihydroxyethylene)bisacrylamide, ethylene, and diallyldiethoxysilane to form magnetic elastomer microspheres, which play a toughening phase role in the plastic substrate and improve the impact resistance of the plastic; then, under the bridging action of methyldihydrogendisiloxane, the elastomer microspheres are polymerized with the side chains of the polyamide molecules to form polysiloxane, which can absorb a large amount of impact energy and achieve the effect of impact resistance; in addition, the magnetic elastic The magnetic microspheres and glass fibers are overlapped to construct a magnetic network, and at the same time, the glass fibers also promote the strengthening and toughening effect of the matrix polyamide; from the comparison of the impact strength experimental data before and after aging of the embodiment and the comparative example, it can be found that the present invention utilizes 3-methoxy-1-bromobenzene and 3-amino-5-carboxyphenylboronic acid to react to obtain a benzophenone compound to prevent the photodegradation of the plastic, and then reacts with 4,4'-diamino-2,2'-bipyridine, copper ion solution, p-fluorobenzoyl chloride, hydroquinone, and trimethylchlorosilane to introduce cuprous ions to inhibit oxidative degradation, and can be continuously regenerated to delay the aging of the plastic. In addition, silicon and boron elements are introduced to form an isolation layer when heated to prevent the plastic from continuing to decompose thermally and oxidatively, thereby enhancing the anti-aging performance of the plastic.

[0084] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing heat-resistant and impact-resistant polyamide plastic, characterized in that: The method comprises the following preparation steps: (1) 3-methoxy-1-bromobenzene, 1,2-dichloroethane and 3-amino-5-carboxyphenylboronic acid were mixed in a mass ratio of 1:16:0.85, placed in an ice bath under argon protection, stirred at 70 rpm for 10 min, and then 0.25 times the mass of Eaton's reagent of 1,2-dichloroethane was added. After stirring for 35 min, the ice bath was removed, and the mixture was stirred at room temperature for 30 min. The mixture was heated to 35°C and reacted for 12 h. The mixture was cooled to room temperature and extracted with water for 3 times. The organic layer was taken and extracted once with saturated brine. The organic layer was taken and dried at 90°C for 5 h to obtain intermediate A. (2) Mix intermediate A and dichloromethane in a mass ratio of 1:130, place in an ice bath under nitrogen protection, stir at 70 rpm for 10 min, add boron tribromide solution 16 times the mass of intermediate A, the mass ratio of boron tribromide to dichloromethane in the boron tribromide solution is 1:4.88, react for 30 min, move to room temperature for 3.5 h, add methanol until no smoke evaporates, then add sodium hydroxide solution until the solution pH is 8.5, separate the liquids, add hydrochloric acid until the solution pH is 4.5, extract with ethyl acetate 3 times, take the organic layer, vacuum degree -0.07 MPa, dry at 55 ° C for 6 h to obtain benzophenone compound; (3) Mix benzophenone compound, 4,4'-diamino-2,2'-bipyridine, triethylamine and tetrahydrofuran in a mass ratio of 1:0.4:1.4:52.5, stir at 60 rpm for 4.5 h, and react at a vacuum degree of -0.09 MPa and 55°C for 4.5 h to obtain intermediate B; (4) Intermediate B and chloroform were mixed in a mass ratio of 1:100, nitrogen was introduced at 80 sccm for 30 min, and then a copper ion solution with a mass ratio of 52 times that of intermediate B was added. The mass ratio of copper tetraethyl cyanide hexafluorophosphate to methanol in the copper ion solution was 1:79.

1. After reacting at 50°C for 6 h, the precipitate was filtered and washed with double distilled water, acetone and anhydrous ether for 5 times, and dried at -0.07 MPa and 50°C for 8 h to obtain a copper complex; (5) Deionized water, copper complex, sodium hydroxide and sodium dodecyl sulfate were mixed in a mass ratio of 7:1:0.5:0.01, stirred and dissolved, and then a p-fluorobenzoyl chloride solution with a mass ratio of 17 times that of the copper complex was added, wherein the mass ratio of p-fluorobenzoyl chloride to dichloromethane in the p-fluorobenzoyl chloride solution was 1:8.

3. After reacting at room temperature for 8 hours, the mixture was filtered, washed with deionized water for 3 times, and dried at 80°C for 4 hours to obtain intermediate C; (6) Under nitrogen protection, the intermediate C, butyl ether, and trimethylchlorosilane were mixed in a mass ratio of 1:4.5:2.2, heated to 160°C, and reacted for 15 hours to obtain a monomer compound. The monomer compound, hydroquinone, potassium carbonate, toluene, and N-methylpyrrolidone were mixed in a mass ratio of 1:0.6:0.6:0.45:3.5, heated to 170°C, kept warm for 30 minutes, heated to 198°C, reacted for 5.5 hours, poured into deionized water while hot, filtered, washed with 90°C deionized water for 5 times, ground to pass through a 25-mesh sieve, washed with 90°C deionized water for 3 times, and dried at 100°C for 6 hours to obtain a homemade polyamide; (7) Waste rubber, sodium dodecylbenzene sulfonate and deionized water were mixed in a mass ratio of 1:1.6:90, and ultrasonicated at 35°C and 600W for 16 min. Then, dibutyl phthalate (3 times the mass of the waste rubber) was added. After activation at 50°C for 54 h, n-heptane (17.5 times the mass of the waste rubber) was added, and the mixture was reacted at 50°C for 27 h to obtain swollen rubber. (8) Deionized water, ferric chloride, ferrous sulfate, and swollen rubber were mixed in a mass ratio of 4:1.7:1.5:1, soaked at 40°C for 4.5 hours, filtered, 11 times the mass of the swollen rubber in a 4% sodium hydroxide solution, reacted at 75°C for 1 hour, and 0.1 times the mass of the swollen rubber in hydrazine hydrate. The mixture was cooled to 50°C, reacted for 30 minutes, magnetically separated, and washed with deionized water until the pH of the washing solution was 7 to obtain magnetic rubber; (9) At 120°C, evacuate to 3Pa, replace with nitrogen three times, introduce ethylene to a pressure of 2MPa, add magnetic rubber, N,N'-(1,2-dihydroxyethylene)bisacrylamide, n-hexane, and diallyldiethoxysilane in a mass ratio of 1:0.35:1.05:0.25, cool to 60°C, add triisobutylaluminum (0.005 times the mass of magnetic rubber) and initiator VOCl3-Al(C2H5)2Cl (0.01 times the mass of magnetic rubber), heat to 150°C, react for 20 minutes, filter, wash with anhydrous ether five times, vacuum -0.07MPa, and dry at 50°C for 6 hours to obtain elastomeric microspheres; (10) The glass fiber was placed in a coupling agent solution at a material-liquid ratio of 1:20, wherein the mass ratio of coupling agent KH-550 to anhydrous ethanol in the coupling agent solution was 1:36.5, and after soaking for 15 minutes, it was taken out, left at room temperature for 1 hour, extracted with xylene for 3 hours, washed with anhydrous ethanol for 3 times, and dried at 120°C for 10 minutes to obtain silane-modified glass fiber; (11) At 15°C, distilled water and 4.5% hydrochloric acid were mixed in a mass ratio of 170:

1. After stirring evenly, homemade polyamide, elastomer microspheres, methyl dihydrogen disiloxane, anhydrous ethanol, 4.5% hydrochloric acid, and isohexadecane were added in a mass ratio of 1:0.25:0.55:0.4:0.05:1.

4. The mass ratio of homemade polyamide to deionized water was 1:0.

6. The temperature was raised to 90°C. After reacting for 3 hours, the mixture was added. Sodium bicarbonate was added until the pH value of the reaction liquid was 7, washed with deionized water for 3 times, diatomaceous earth (0.3 times the mass of the homemade polyamide) was added, allowed to stand for 30 minutes, filtered, dried at 50°C and vacuum degree of -0.07MPa for 5 hours, silane-modified glass fiber and stearate were added in a mass ratio of 1:0.1, and the mass ratio of silane-modified glass fiber to homemade polyamide was 0.1:

1. After stirring and mixing, extruded at 190-230°C, and pelletized to obtain heat-resistant and impact-resistant polyamide plastic.

Citation Information

Patent Citations

  • Glass-fiber-reinforced PA66 / PBT (polyamide 66 / polybutylene terephthalate) resin alloy material and preparation method thereof

    CN103013109A

  • Tough thermoplastic nylon compositions and processes for preparing them

    EP0051471A1